No longer invisible: religion in university education - Jacobsen, Rhonda Hustedt (Oxford University Press, 2012)
Drawing on interviews with hundreds of university professors co-curricular educators, administrators, and students from public and private colleges and universities across the United States, Douglas and Rhonda Hustedt Jacobsen demonstrate that religion is essential for the work of higher education in the 21st century